PREGNANT WOMAN WITH COVID 19 AND DIABETES MELLITUS WITH AN UNFAVORABLE OUTCOME: Pregnancy and COVID 19 - Gamarra-Manrique, Renzo R. (2021)
We present a case of a 35-year-old elderly multigesta, who had a gestation of 25 weeks and infection by SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2). She had a history of diabetes mellitus II with irregular treatment and controls. The patient was asymptomatic for 5 days after diagnosis, presenting respiratory distress and sensorial compromise within 24 hours. She was admitted as an emergency, presenting multiple organ failure and lack of fetal heartbeat, for which she was transferred to the ICU (Intensive Care Unit). A caesarean section was performed after hemodynamic compensation. The product is a 24-week stillbirth. She continues with treatment in the ICU, where she dies 19 days later. It is recommended to consider closer monitoring in pregnant women with concomitant diseases, such as diabetes